2017
DOI: 10.1088/1748-605x/aa7608
|View full text |Cite
|
Sign up to set email alerts
|

An acid-free water-born quaternized chitosan/montmorillonite loaded into an innovative ultra-fine bead-free water-born nanocomposite nanofibrous scaffold; in vitro and in vivo approaches

Abstract: An acid-free water-born chitosan derivative/montmorillonite has been successfully synthesized. A natural-based biopolymer, N-(2-hydroxy) propyl-3-trimethyl ammonium chitosan chloride, was synthesized, and its structure confirmed by Fourier transform infrared microscopy and conductometric titration. It was applied to the cationic ion-exchange reaction of montmorillonite. Then, the synthesized materials were used to produce water-born composite scaffolds for tissue engineering applications and formed an ultra-fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…Khlibsuwan et al reported the preparation of drug loaded chitosanclay nanocomposite microparticles with an intercalated nanocomposite structure [28]. Chitosan-based ultra-fine beadfree water-born nanocomposite nano-fibrous scaffolds have been successfully synthesized by Dastjerdi et al [29] and they are considered as promising drug delivery systems with dual controlled drug release and multi-purpose targeting therapies. Two types of chlorophyllin functionalized GO nanostructures as strong antibacterial agents were fabricated and their antibacterial mechanisms were proposed that the synergistic antibacterial effects existed among GO, chlorophyllin and leached Zn 2+ [30].…”
Section: Introductionmentioning
confidence: 99%
“…Khlibsuwan et al reported the preparation of drug loaded chitosanclay nanocomposite microparticles with an intercalated nanocomposite structure [28]. Chitosan-based ultra-fine beadfree water-born nanocomposite nano-fibrous scaffolds have been successfully synthesized by Dastjerdi et al [29] and they are considered as promising drug delivery systems with dual controlled drug release and multi-purpose targeting therapies. Two types of chlorophyllin functionalized GO nanostructures as strong antibacterial agents were fabricated and their antibacterial mechanisms were proposed that the synergistic antibacterial effects existed among GO, chlorophyllin and leached Zn 2+ [30].…”
Section: Introductionmentioning
confidence: 99%
“…These peaks are attributed to the deformation vibration peak and the stretching vibration peak of –CH 3 in the quaternary ammonium group of HTCC. Thus, the –NH 2 groups of chitosan are replaced with the –CH 2 CH(OH)CH 2 N + (CH 3 ) 3 Cl − group, which demonstrates HTCC ( Figure 1 ) [ 38 40 ].…”
Section: Resultsmentioning
confidence: 99%